Capitalism and the politics of happiness - Isaacs, Dean (PINS-Psychology in Society, 2018)
[Book Rew] Davies, William (2015) The happiness industry: How government and big business sold us well-being. London: Verso. ISBN 978-1-78168-845-8 hbk. Pages 314 This book is an interesting commentary and concise analysis of the plethora of philosophical, scientific, social scientific, economic and psychological forays into the measurement, and utilitarian deployment of happiness as both a subjective experience, and an objectively measurable aspect of human beings. It is, seemingly, not premised on any empirical research carried out by the author. The book charts the emergence of happiness as a domain of inquiry and its importance in the emergence of technologies of psychological control. The book focusses on the Benthamite/Behaviourist tradition within the human and social sciences, but also looks at the emergence of neuroscience as a major contributor to both the understanding of happiness, and the instrumentalization of happiness in the pursuit of specific economic and social outcomes.